Proses Produksi Program Acara “Assalamualaikum” Di TV Alhijrah Dalam Perspektif Dakwah - Khairuizzah Helmi Azhar; Achmad Syarifuddin; Muhammad Randicha Hamandia (CV. ITTC INDONESIA, 2023)
This thesis is entitled Production Process of the Assalamualaikum Program on Al-Hijrah TV from a Da'wah Perspective. The aim of this research is to determine the production process of Assalamualaikum on Al Hijrah Television from the production preparation stage to the post-production stage from a da'wah perspective and to find out the delivery of da'wah through the production process to the preparation of programs to convey the da'wah to the public. The research method used in this thesis is a qualitative method, the researcher used program manager, producer and cameraman as informants. Data collection in this research used interviews, observation, documentation and data analysis techniques used in this research, namely data reduction, data presentation and drawing conclusions. The results obtained from this research, Firstly, the dynamic renewal of TV AlHijrah which presents information programs and Islamic programs in Malaysia has now won the hearts of viewers. The program